Orientation control of anisotropic microparticles under magnetic fields - Chua, Clarence (Nanyang Technological University, 2020)
It has always been a challenge to alter and influence the microstructure of ceramics and composites that possess high concentration in solid because of its high viscosity. Recently, a new method was developed and applied to make periodic porous assemblies or dense ceramics, but not composites. This method, known as magnetically assisted slip casting, allows the manipulation of magnetically responsive microparticles within the material by employing the use of rotating magnets, which results in the ability to build the desired microstructure. Moreover, it has been predicted that alternating layers of horizontal and vertical orientations of the microparticles within the microstructure act as a barrier to inhibit crack propagation. This inhibition of crack propagation increases the amount of stress the material can absorb before fatigue fracture. In this report, a set-up was carefully designed and used to both automate and execute the magnetically assisted slip casting process to demonstrate the ability of control over the creation of programmable horizontal and vertical layers. The resulting cake sample exhibited positive results by means of visual observation. Due to the nature of the alternating vertical and horizontal alignments of the micro-platelets, the samples produced had visible light and dark colored alternating layers corresponding to the orientations of the micro-platelets. This shall be discussed further later in the report. The resulting samples can then be tested to ascertain that the enhancements in the hardness of the material were due to the new microstructure in the composite and the relationship between the hardness variation between different samples was also explored. Its enhanced properties can then be determined to be a function of the layer thickness.